Carotid bodies contribute to sympathoexcitation induced by acute salt overload. Issue 1 (10th November 2018) - da Silva, Elaine Fernanda; Bassi, Mirian; Menani, José Vanderlei; Colombari, Débora Simões Almeida; Zoccal, Daniel Breseghello; Pedrino, Gustavo Rodrigues; Colombari, Eduardo
Abstract : New Findings: What is the central question of this study? Does carotid body input contribute to the hyperosmotic responses? What is the main finding and its importance? The response to NaCl overload is sympathorespiratory excitation. Eliminating the carotid body input reduced sympathoexcitation but did not affect the increase in phrenic burst frequency, whereas eliminating the hypothalamus prevented the tachypnoea and sympathoexcitation. We conclude that the carotid body inputs are essential for the full expression of the sympathetic activity during acute NaCl overload, whereas the tachypnoea depends on hypothalamic mechanisms. Abstract: Acute salt excess activates central osmoreceptors, which trigger an increase in sympathetic and respiratory activity. The carotid bodies also respond to hyperosmolality of the extracellular compartment, but their contribution to the sympathoexcitatory and ventilatory responses to NaCl overload remains unknown. To evaluate their contribution to acute NaCl overload, we recorded thoracic sympathetic (tSNA), phrenic (PNA) and carotid sinus nerve activities in decorticate in situ preparations of male Holtzman rats (60–100 g) while delivering intra‐arterial infusions of hyperosmotic NaCl (0.17, 0.3, 0.7, 1.5 and 2.0 mol l −1 ; 200 μl infusion over 25–30 s, with a 10 min time interval between solutions) or mannitol (0.3, 0.5, 1.0, 2.7 and 3.8 mol l −1 ) progressively. The cumulative infusions of hyperosmotic NaCl increased the perfusate osmolality to 341 ± 5 mosmol (kg water) −1 and elicited an immediate increase in PNA and tSNA ( n = 6, P < 0.05) in sham‐denervated rats. Carotid body removal attenuated sympathoexcitation ( n = 5, P < 0.05) but did not affect the tachypnoeic response. A precollicular transection disconnecting the hypothalamus abolished the sympathoexcitatory and tachypnoeic responses to NaCl overload ( n = 6, P < 0.05). Equi‐osmolar infusions of mannitol did not alter the PNA and tSNA in sham‐denervated rats ( n = 5). Sodium chloride infusions increased carotid sinus nerve activity ( n = 10, P < 0.05), whereas mannitol produced negligible changes ( n = 5). The results indicate that carotid bodies are activated by acute NaCl overload, but not by mannitol. We conclude that the carotid bodies contribute to the increased sympathetic activity during acute NaCl overload, whereas the ventilatory response is mainly mediated by hypothalamic mechanisms. Abstract :